Eﬃcacy of an expanded integrative rehabilitation approach in patients with Guillain-Barre syndrome: a case series - Mkrtchyan, Hasmik; Simonyan, Erik; Kamrany, Reyhaneh; Martirosyan, Narine (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. The work aims to present the design of the physical rehabilitation program used in cases of Guillain-Barre syn-drome in conditions of the neurorehabilitation department.Methods. The work includes a description of three cases with Guillain-Barre syndrome. To assess the eﬀectiveness of the rehabilitation strategy, the sensory assessment was performed according to the INCAT testing system and the muscle assess-ment – based on a 0–5 scale of manual testing. The patients underwent an assessment for general motor skills and orthostatic hypotension. Pain syndrome was assessed on a 10-point scale. The rehabilitation strategy included diﬀerent interventional approaches and a large volume of functional and task-oriented exercises designed according to the method for the 4th degree of the Hughes scale targeting diﬀerent motor skills of the patients.Results. Improvement was observed in all tested movements of patients. For a proportion of tested movements, the diﬀerences between the initial and ﬁnal testing scores were signiﬁcant. All pain and sensory assessment results showed signiﬁcant im-provement.Conclusions. The very small sample of patients was not enough to show the impact of the designed intervention on all out-comes, but the designed expanded strategy could be used in a future case-control study with a large group of participants to evidence the eﬃcacy of the expanded cluster of interventions.
Keywords: Guillain-Barre syndrome; physical rehabilitation; muscle strength; functional rehabilitation; adaptation